Digital Human Modeling Trends in Human Algorithms - Cai, Yang.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2008)
The emerging information technologies have given rise to new human patterns in terms of both physiological and psychological interactions. Human Algorithms aim to model human forms, interactions, and dynamics in this new context. They are becoming increasingly comprehensive and inexpensive for use in real-world designs: inside monitors, connected to networks, and under human skin. This book aims to reflect the state-of-the-art of Digital Human Modeling, specifically emergent Human Algorithms. It constitutes a survey of innovative ideas aimed at a wide range of readers, including college students, researchers, engineers, designers, scientists, managers, and healthcare professionals. The 11 chapters are divided into three parts: Human Dynamics, Virtual Humans and Human Forms.
Human Dynamics -- Implantable Computing -- Brainwave-Based Imagery Analysis -- Visual Digest Networks -- Virtual Humans -- Biomedical Modeling in Tele-Immersion -- Virtual Fit Study of Pediatric Heart Assist System -- Virtual Clinical Therapy -- Virtual Human Problem-Solving Environments -- Biomechanical Modeling from In-Vivo Data -- Human Forms -- Natural Form Modeling -- Augmented Privacy with Virtual Humans -- 3D Facial Recognition with Soft Computing -- Digital Human Modeling.
Keywords: Computer science; Computer communication systems; User interfaces (Computer systems).; Artificial intelligence; Computer simulation; Bioinformatics; Computers and civilization; Computer Science; Artificial Intelligence (incl. Robotics).; Simulation and Modeling; User Interfaces and Human Computer Interaction; Computational Biology/Bioinformatics.; Computer Communication Networks; Computers and Society; Electronic books